2016
DOI: 10.1177/1933719116630414
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Systemic Levels of Endocannabinoids and Related Mediators Across the Menstrual Cycle in Women With Endometriosis

Abstract: Cannabinoids and modulators of the endocannabinoid system affect specific mechanisms that are critical to the establishment and development of endometriosis. The aim of this study was to measure the systemic levels of endocannabinoids and related mediators in women with and without endometriosis and to investigate whether such levels correlated with endometriosis-associated pain. Plasma and endometrial biopsies were obtained from women with a laparoscopic diagnosis of endometriosis (n = 27) and no endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 47 publications
7
44
2
1
Order By: Relevance
“…These findings are in accordance with previously published studies showing TRPV1 expression in ectopic endometrial epithelial cells [101]. The presence of this receptor in endometrial tissue and the elevated levels of eCB in patients with endometriosis may therefore be associated with the development of chronic inflammatory pain [99]. …”
Section: The Ecs In Gynecological Disorders and Cancersupporting
confidence: 82%
See 3 more Smart Citations
“…These findings are in accordance with previously published studies showing TRPV1 expression in ectopic endometrial epithelial cells [101]. The presence of this receptor in endometrial tissue and the elevated levels of eCB in patients with endometriosis may therefore be associated with the development of chronic inflammatory pain [99]. …”
Section: The Ecs In Gynecological Disorders and Cancersupporting
confidence: 82%
“…There were, however, no changes in CB 1 expression in endometrial stromal cells during the menstrual cycle of the women with endometriosis, although in the healthy controls (and in contrast to findings by Bilgic et al [100]) an upregulation of CB 1 was found in the S-phase [99]. TRPV1, an ECS-related receptor, was found to be expressed at comparable levels in ectopic endometrial stromal cells from both healthy controls and women with endometriosis [99]. These findings are in accordance with previously published studies showing TRPV1 expression in ectopic endometrial epithelial cells [101].…”
Section: The Ecs In Gynecological Disorders and Cancermentioning
confidence: 89%
See 2 more Smart Citations
“…Elevated microdialysate levels of PEA and SEA sampled from the trapezius muscle have been reported in subjects with chronic neck/shoulder pain (n=11) compared to healthy controls (n=11) [135]. Finally, one study found that endometriosis (n=27) was associated with elevated plasma levels of AEA, OEA, and 2-AG compared to controls (n=29) [136]. To the best of my knowledge, with the exception of the two studies included in this thesis, only two previous studies have investigated EC and NAE plasma levels in CWP/FMS.…”
Section: Ec System and Naes In Human Pain Studiesmentioning
confidence: 99%